Zooplankton of Boztepe Recai Kutan Dam Lake (Malatya - Turkey) - Saler, Serap; Alpaslan, Kenan; Karakaya, Gokhan; Gunduz, Fatih (Ege Univ, Fac Fisheries, 2017)
Water samples taken from Boztepe Dam Lake monthly between January - December 2014 period were observed in terms of zooplankton. During the study, a total of 33 zooplankton species, 17 species from Rotifera, 13 species from Cladocera and 3 species from Copepoda were identified. Maximum number of zooplankton has been recorded in May (271785 individuals/m(3)). The least the number of individuals were recorded in February (5090 individuals/m(3)). The maximum number of taxa were recorded in October with 17 species and the least were recorded in february with 5 species. All of the zooplanktonic species have been detected for the first time in Boztepe Recai Kutan Dam Lake. Based on the total number of individuals of zooplankton, Rotifera was dominant group in the dam lake (51.5%) followed by Cladocera (39.4 %) and Copepoda (9.1 %). Dominant Rotifera species was Keratella cochlearis followed by K. quadrata. Bosmina longirostris was dominant Cladocera species. Cyclops vicinus was the most observed Copepoda species. Rotifera has showed higher diversity compared to other groups, reaching also high densities throughout the study period. Keratella cochlearis K. quadrata, Bosmina longirostris are indicators of eutrophic character and were recorded frequently in high numbers, suggest that the lake may be eutrophic.
Keywords: Rotifera; Cladocera; Copepoda; Boztepe Recai Kutan Dam Lake